Nanomedicines for the Efficient Treatment of Intracellular Bacteria: The “ART” Principle - Qi, Hongzhao; Shan, Peipei; Wang, Yin; Li, Peifeng; Wang, Kun; Yang, Lijun (Frontiers in Chemistry, 2021)
Infections induced by bacteria at present are a severe threat to public health. Compared with extracellular bacteria, intracellular bacteria are harder to get rid of and readily induce chronic inflammation as well as autoimmune disorders. As the development of new antibiotics becomes more and more difficult, the construction of new antibiotic dosage forms is one of the optimal choices for the elimination of intracellular bacteria, and, to date, various nanomedicines have been exploited. However, current nanomedicines have limited treatment efficiency for intracellular bacteria due to the multiple biological barriers. Here in this short review, we focus on systemically administered nanomedicines and divide the treatment of intracellular bacteria with nanomedicines into three steps: (Ⅰ) Accumulation at the infection site; (Ⅱ) Recognition of infected cells; (Ⅲ) Targeting of intracellular bacteria. Furthermore, we summarize how nanomedicines are elaborately designed to achieve the "ART" principle and discuss the problems of experimental models construction. Through this review, we want to remind that the golden approach for the building of cell and animal experimental models should be established, and nanomedicines should be also endowed with the versatility to follow the "ART" principle, efficiently improving the treatment efficiency of nanomedicines for intracellular bacteria.